Education for professional chaplaincy in the US: mapping current practice in Clinical Pastoral Education (CPE). Issue 4 (2nd October 2021) - Clevenger, Casey; Cadge, Wendy; Stroud, Irene Elizabeth; Palmer, Patricia K.; Haythorn, Trace; Fitchett, George
Abstract: In light of questions that have been raised about education for professional healthcare chaplaincy, we examined the skills and knowledge Clinical Pastoral Educators believe students need to perform the essential tasks and responsibilities of a chaplain. At 19 recently re-accredited ACPE centers across the country, we asked educators about the knowledge chaplains need to be effective, the specific content areas they teach, and how didactic education is planned and organized within their programs. Beyond a focus on religious diversity, we found little consensus among educators regarding a core knowledge base that should be taught during CPE. While most respondents in our study recognize the importance of didactic education in preparing students to become chaplains, there is a lack of consistency in didactic curricula across programs. Our findings suggest the need for broader conversation and collaboration among educators, national chaplaincy organizations, and theological schools regarding the goals, priorities, and outcomes of CPE.